2017
DOI: 10.2495/dne-v11-n4-703-711/024
|View full text |Cite
|
Sign up to set email alerts
|

Agents Within a Developmental Complex Adaptive System: Intrauterine Male Hormones and Dental Arch Size in Humans

Abstract: Oral development is a complex adaptive system influenced by genetic, epigenetic and environmental factors. The dental arch develops from 6 weeks in utero until adult life, forming an accessible record to study general growth and development. Increased tooth size in female dizygotic opposite-sex (DZOS) twins compared with female dizygotic same-sex (DZSS) twins provides evidence for the masculinisation of females gestated with a male co-twin, possibly due to the intrauterine influence of male sex hormones: the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…3 Teeth and dental arches were analyzed with the help of a previously validated bidimensional image analysis method. 4,5 Increased correlation coeffi cients were found, in several studies, for the bidimensional image analysis method, with small errors of method for all parameters. [5][6][7] A previous study showed excellent coefficients of reliability for dental morphometric measurements.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…3 Teeth and dental arches were analyzed with the help of a previously validated bidimensional image analysis method. 4,5 Increased correlation coeffi cients were found, in several studies, for the bidimensional image analysis method, with small errors of method for all parameters. [5][6][7] A previous study showed excellent coefficients of reliability for dental morphometric measurements.…”
Section: Resultsmentioning
confidence: 88%
“…4,5 Increased correlation coeffi cients were found, in several studies, for the bidimensional image analysis method, with small errors of method for all parameters. [5][6][7] A previous study showed excellent coefficients of reliability for dental morphometric measurements. The intra-operator reliability of these measurements was found to be in the Excellent category.…”
Section: Resultsmentioning
confidence: 88%
“…Proses kalsifikasi gigi insisif sentral maksila permanen dimulai pada usia 3-4 bulan setelah kelahiran dan kalsifikasi mahkota gigi umumnya selesai sekitar 3-4 tahun seteleh gigi erupsi. 9,10 Waktu erupsi gigi insisif sentral sekitar usia 6-7 tahun.Pembentukan akar pada umumnya selesai pada usia 10 tahun ditandai dengan foramen apikal yang telah tertutup sempurna dan menunjukkan bahwa pertumbuhan panjang gigi telah selesai. 10 Pertumbuhan manusia dipengaruhi oleh banyak faktor seperti genetik, hormon, jenis kelamin, nutrisi, ras, dan lingkungan.…”
Section: Pembahasanunclassified